Pengembangan Sistem Kendali Robot Humanoid untuk Edukasi berdasarkan Robosapien dan Raspberry Pi Zero - Heri Ngarianto; Alexander A. S. Gunawan (Bina Nusantara University, 2020)
In order to help students be more interested in learning about programming both at school and at home, we have designed educational toys in the form of humanoid robot. In this paper, intelligent robot movement control systems are developed, thus the students can interact directly and learn programming on human robots. For building a low-cost humanoid robot, we modified low-cost robot toy, that is Robosapien from Wowwee by embbeding a control system. The control system is developed based on Raspberry Pi Zero W, which enables us to control Robosapien's movements wirelessly. This learning media is expected to enhance the student’s spirit of learning, especially in the field of robotics and programming. The main contribution of the research is the description and analysis of various design decisions during the development of this humanoid robot. In addition, it provides information about the main components for development and example for interacting with robots as learning media.